A traumatic experience faced by the second wife married in a polygamous marriage. A challenge to pastoral care. A story of the proposed contribution of a modern pastoral care, and councelling model to the second wives, married in a polygamous marriage, with special reference to the people of Mogale circut at Mogale Methodist Church of Southern Africa in Gauteng Province - Masango, Maake J.S (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2011.